Perhitungan Tarif INA-CBG Terhadap Tarif Real Rumah Sakit Dengan Menggunakan Metode Activity Based Costing Pada Pasien PPOK - Handa Meru Erio Rakihara; Titiek Hidayati (Fakultas Ilmu Kesehatan, 2020)
ABSTRACT Chronic Obstructive Pulmonary Disease (COPD) is a disease with limit airway characteristics that not completely reversible. Airway limitation usually progressive and correlates with inflammation response due to harmful material or gas. The Burden Of Disease Study under auspices of The World Health Organization stated that COPD is the cause of death, who previously ranked 6th and in 2020 it can become 3rd as the most common cause of death. Respira Lung Hospital Yogyakarta accepts general patient and patient with insurance, also they already cooperate with BPJS, with the result that replacement of BPJS patient’s payments are adjusted to Indonesia Case Base Groups rates in accordance with type classification and regionality. This study has the goal to count unit cost using Activity Based Costing (ABC) method in Chronic Obstructive Pulmonary Disease patient’s care and to compare it with real cost and INA-CBG’s fare.This research is using descriptive qualitative with case study design in Respira Lung Hospital Yogyakarta, the chosen cases are patients that already diagnosed ICD X : J-4-17-III (Chronic Obstructive Pulmonary Disease). Result : The result of unit cost calculation on Chronic Obstructive Pulmonary Disease patient with ABC method is Rp 4.851.150,00 consist of direct cost Rp 1.735.050,00 and overhead cost Rp 3.116.100,00. According to unit cost calculation for Chronic Obstructive Pulmonary Disease patient it counts Rp 4.851.150,00 and has difference Rp 2.134.450,00 with real cost in Respira Lung Hospital Yogyakarta and Rp 1.442.814,00 with INA CBG’s fare. Keyword: Activity Based Costing (ABC), Chronic Obstructive Pulmonary Disease, Unit Cost